The 30th Anniversary Russian Gastroenterology Congress and the Meeting of the Profile Commission on Gastroenterology of the Ministry of Health of the Russian Federation - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2025)
.